Dynamics and Molecular Mechanism of Phosphate Binding to a Biomimetic Hexapeptide - Zhai, H.; Qin, L.; Zhang, W.; Putnis, Christine; Wang, L. (American Chemical Society, 2018)
© 2018 American Chemical Society. Phosphorus (P) recovery from wastewater is essential for sustainable P management. A biomimetic hexapeptide (SGAGKT) has been demonstrated to bind inorganic P in P-rich environments, however the dynamics and molecular mechanisms of P-binding to the hexapeptide still remain largely unknown. We used dynamic force spectroscopy (DFS) to directly distinguish the P-unbound and P-bound SGAGKT adsorbed to a mica (001) surface by measuring the single-molecule binding free energy (?Gb). Using atomic force microscopy (AFM) to determine real-time step retreat velocities of triangular etch pits formed at the nanoscale on the dissolving (010) face of brushite (CaHPO4·2H2O) in the presence of SGAGKT, we observed that SGAGKT peptides promoted in situ dissolution through an enhanced P-binding driven by hydrogen bonds in a P-loop being capable of discriminating phosphate over arsenate, concomitantly forming a thermodynamically favored SGAGKT-HPO42- complexation at pH 8.0 and relatively low ionic strength, consistent with the DFS and isothermal titration calorimetry (ITC) determinations. The findings reveal the thermodynamic and kinetic basis for binding of phosphate to SGAGKT and provide direct evidence for phosphate discrimination in phosphate/arsenate-rich environments.